“Drug Repurposing” Policies and Statutes: Lessons from the COVID-19 Pandemic: A Review - Ravi, Srividya; Jadhav, Sammita; Ghooi, Ravindra (Indian Journal of Pharmaceutical Education and Research, 2023)
Introduction: Repurposed drugs are not eligible for patent protection in India vide Sec 3 (d) of the Indian Patent Act, 1970. The data generated to establish the therapeutic efficacy of the repurposed drugs for the new indication are not eligible for data exclusivity under the provisions of the Drugs and Cosmetic Act, 1940. However, repurposed drugs possess immense advantages, especially when compared to the traditional route of drug discovery. Marketing repurposed drugs is fraught with challenges, and means to overcome them need to be facilitated. Methodology: A review of literature regarding provisions available to protect repurposed candidates through various routes globally were studied including policies, special committee reports as well as case laws. Results: A brief tenure of data exclusivity for repurposed candidates as provided in statutes in the US and EU appears to be an attractive route of protection of such inventions. This will encourage and incentivize drug research by this route and eventually lead to a fulfillment of India being a preferred destination for not only pharma manufacturing, but also research.
Keywords: Repurposing drugs; Patents; Data exclusivity; COVID-19; Drug discovery; Drug development in India